Identification and characterisation of elongation factor Tu, a novel protein involved in Paracoccidioides brasiliensis-host interaction - Marcos, Caroline Maria [UNESP]; de Oliveira, Haroldo Cesar [UNESP]; da Silva, Julhiany de Fátima [UNESP]; Assato, Patricia Akemi [UNESP]; Yamazaki, Daniella Sayuri [UNESP]; da Silva, Rosângela Aparecida Moraes [UNESP]; Santos, Cláudia Tavares [UNESP]; Santos-Filho, Norival Alves [UNESP]; Portuondo, Deivys Leandro [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Fusco-Almeida, Ana Marisa [UNESP] (Oxford University Press (OUP), 2016)
Paracoccidioides spp., which are temperature-dependent dimorphic fungi, are responsible for the most prevalent human systemic mycosis in Latin America, the paracoccidioidomycosis. The aim of this study was to characterise the involvement of elongation factor Tu (EF-Tu) in Paracoccidioides brasiliensis-host interaction. Adhesive properties were examined using recombinant PbEF-Tu proteins and the respective polyclonal anti-rPbEF-Tu antibody. Immunogold analysis demonstrated the surface location of EF-Tu in P. brasiliensis. Moreover, PbEF-Tu was found to bind to fibronectin and plasminogen by enzyme-linked immunosorbent assay, and it was determined that the binding to plasminogen is at least partly dependent on lysine residues and ionic interactions. To verify the participation of EF-Tu in the interaction of P. brasiliensis with pneumocytes, we blocked the respective protein with an anti-rPbEF-Tu antibody and evaluated the consequences on the interaction index by flow cytometry. During the interaction, we observed a decrease of 2- and 3-fold at 8 and 24 h, respectively, suggesting the contribution of EF-Tu in fungal adhesion/invasion.
Keywords: EF-Tu; fibronectin; fungal-host interaction; moonlighting protein; Paracoccidioides brasiliensis; plasminogen